2019
DOI: 10.1039/c8py01749b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high molecular weight isobutylene-α-methylstyrene copolymers containing alkenyl groups with a half sandwich scandium initiator system under mild conditions

Abstract: Copolymerizations of isobutylene and two alkenyl functionalized α-MeSt derivatives respectively, catalyzed by [(C5Me4SiMe3)Sc(CH2SiMe3)2THF], at −35 °C produced high Mn random copolymers with pendant alkenyl groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Glass transition temperature and compositions of (a) MMA–VDC copolymers (data from ref ) and MMA–IB copolymers (data from ref ) and (b) αMS–IB copolymers (data from ref ).…”
Section: More Complex Casesmentioning
confidence: 87%
See 1 more Smart Citation
“…Glass transition temperature and compositions of (a) MMA–VDC copolymers (data from ref ) and MMA–IB copolymers (data from ref ) and (b) αMS–IB copolymers (data from ref ).…”
Section: More Complex Casesmentioning
confidence: 87%
“…Data of MMA–VDC and MMA–IB copolymers in Figure a seem to support these predictions. However, this conclusion requires more data to test because Yang et al . recently reported an opposite example that αMS–IB copolymers showed a negative deviation in the high IB content region (>78%, Figure b).…”
Section: More Complex Casesmentioning
confidence: 99%
“…RIS is a generalized conformational approach dependent on the types of comonomers, as each bond pair is explicitly examined and all energy levels are statistically summed along any specific chain connectivities, e.g., any regio-, stereo-, or comonomer-sequence distributions can be explicitly considered. Thus it has great potential in future studies to explain the more peculiar comonomer sequence dependent Tgp deviations observed for AD-SD type comonomers [23]. In addition, similar to stereosequence dependence of local conformational geometry and subsequently the dynamics of the glass transition process [24], comonomer sequence dependence of glass transition dynamics of copolymers with tunable chain architectures can be studied in combined experimental and simulation studies which ultimately contribute to the understanding of the molecular bases of polymer glass transition phenomena.…”
Section: Current Status and Future Perspectivesmentioning
confidence: 99%
“…[31,32] According to the IB polymerization of polyisobutylene (PIB) in our research, the synthesis of well-defined copolymer of IB and St can be controllable within the scandium initiator system. [23,33,34] As a result, we attempted to synthesize the copolymers with sPS blocks and PIB blocks, in order to create novel materials combining the favorable properties of both sPS and PIB.…”
Section: Introductionmentioning
confidence: 99%